2023
DOI: 10.3390/life13020421
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between Bone Mineral Density and Progression of Hip Osteoarthritis in Adult Men and Women in Bulgaria—Results from a 7-Year Study

Abstract: Changes in clinical presentation, radiographic progression (RP), bone mineral density (BMD), bone turnover (BT), and cartilage turnover (CT) markers were compared in two groups of patients with hip osteoarthritis (HOA) over a period of 7 years. Each group consisted of 150 patients, including a control group on standard-of-care therapy (SC) with simple analgesics and physical exercises, and a study group (SG) on standard-of-care therapy supplemented by vitamin D3 and intravenous administration of zoledronic aci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(12 citation statements)
references
References 50 publications
0
1
0
Order By: Relevance
“…We performed additional statistical processing of patient data from two published, double-blinded, randomized, and placebo-controlled studies (DB-RCTs), which tested the effect of ia-CS, ia-HA (KИ-109-3-0008/14.01.2014) [31], and iv-BP (ZA) [34] -KИ-109-3-0009/14.01.2014 www.bda.bg. The results were compared with the country's standard pHOA-D3 supplementation according to serum levels (20-120 ng/mL; target level of 60 ng/mL), simple analgesics (paracetamol, up to 2.0 g/24 h), and physical exercises.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We performed additional statistical processing of patient data from two published, double-blinded, randomized, and placebo-controlled studies (DB-RCTs), which tested the effect of ia-CS, ia-HA (KИ-109-3-0008/14.01.2014) [31], and iv-BP (ZA) [34] -KИ-109-3-0009/14.01.2014 www.bda.bg. The results were compared with the country's standard pHOA-D3 supplementation according to serum levels (20-120 ng/mL; target level of 60 ng/mL), simple analgesics (paracetamol, up to 2.0 g/24 h), and physical exercises.…”
Section: Methodsmentioning
confidence: 99%
“…Among the respective RPs are established differences in radiograph progression [15][16][17][18][19][20][21], as well as differences in biomarkers of bone, cartilage, and synovial turnover [22][23][24][25], and in total and local bone mineral density (BMD) [26][27][28]. There are different therapeutic responses to different pharmacologic medications: ia-CS [29][30][31], ia-HA [31], NSAIDs, antibodies to neuronal growth factor [24,25], and oral and intravenous bisphosphonates [32][33][34]. At present, there are four established basic endophenotypes of primary HOA based upon RPs, BMD, and markers of bone, cartilage, and synovial turnover [22][23][24][25]35]: hypertrophic ('H'-HOA), intermediate ('I'-HOA), atrophic ('A'-HOA), and rapidly progressive ('RP'-HOA).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, E2 treatment protected against ovariectomy-induced loss of subchondral trabecular bone [123]. While zoledronate acid improved clinical symptoms and delayed THA in patients with HOA with increased bone turnover [124], some studies have reported its non-protective effect against KOA [125]; hence, its protective effects remain inconclusive. Sr ranelate has been widely reported for its efficacy against OA [126,127].…”
Section: Osteoporosis Treatments and Osteoarthritismentioning
confidence: 99%
“…Later, the occurrence rate of the different patterns and their association with the clinical and radiological progression of HOA were determined [40][41][42] and a suggestion of presence of different phenotypes in HOA was made [43,44]. The studies on the association between osteoporosis and the pathogenesis and progression of HOA, based on the Rotterdam cohort study [45][46][47], and others [48] proved that 'A'-patterns are associated with a low regional (FN-BMD/TH-BMD) and whole body (LS-BMD and TB-BMD) bone mineral density and a rapid radiographic progression, while 'H'patterns are associated with an increased local BMD and a slow radiographic progression [45][46][47][48]. Currently, HOA radiographic patterns are defined based on the balance between the processes of narrowing of the joint space (as a result of AC -loss) and the processes of SB remodeling with the growth of osteophytes, subchondral sclerosis and the formation of bone cysts, all of them being included in the OARSI atlas for defining HOA [49].…”
Section: Patientsmentioning
confidence: 99%
“…But it is important to remember that the 'RPs' of the HOA reflects the changes mainly in the SB, i.e. their meaning is different depending on the type of therapeutic intervention.With interventions directly influencing the SB (therapies with bisphosphonates, strontium ranelate, teriparatide, calcitonin, oateoprotegerin) -the changes in SB occur faster and are significant, the importance of RPs is more pronounced and is demonstrated earlier [48,76,77]. On the contrary -with interventions influencing mainly AC (IA-HA, IA-PRP -platelet rich plasma, mesenchymal stem cells -MSCs) [24,[29][30][31][32][33][34][35][36][37][78][79][80][81][82][83] or ST /SS -the smoldering synovitis (IA-CS, methotrexate, anti inflammatory cytokines) [23][24][25][26][27][84][85][86] -the changes in SB are delayed in time and not so obvious, and the influence of RPs on the obtained results occurs later in time and is not so dramatic.…”
Section: Analyses Of the Drop-out Patients Showed Two Types Of Differ...mentioning
confidence: 99%